Flexural Behaviour of 3DCP Beams with Expanded Metal Sheet Reinforcement: Experimental Investigation and Numerical Verification - Reznik , Petro; Petrenko, Dmytro; Volodymyrov, Anton; Alataiev, Dzhamaldii (Academic journal Industrial Machine Building Civil Engineering, 2025)
An experimental and numerical study of the flexural behavior of 3D-printed concrete (3DCP) beams reinforced with expanded metal sheet are presented in this paper. Four-point bending tests on beams of 3DCP were carried out in accordance with DSTU B V.2.7-214:2009, recording load–deflection curves and strains. The 3DCP showed an equivalent axial tensile strength 30–45 % lower than that of class C16/20 concrete. Correctly oriented sheet reinforcement increased failure load and flexural toughness by about 30–40 %, while a 3D FE model in LIRA-FEM reproduced ultimate loads within 5–10 % but underestimated stiffness.